The effect of parent-child relationship styles on the social adjustment of the adolescent girls. - Arjmand Nasimi, Reyhaneh; Bagheri, Fariborz (International Journal of Applied Behavioral Sciences, 2016)
Introduction: The purpose of this study was to examine and compare the social adjustment in balanced and non-balanced patterns of the parent-child relationship. Methods: The research population was all female gifted students in the Farzanegan high school in the first educational district of Tehran in 2013-14. The sample research included 96 female gifted students who answered the parent-child relationship model questionnaire and the social adjustment subscale of the Bell adjustment inventory. After scoring their responses and removing uncompleted ones, Sample population was divided into three groups of: the balanced, the non-balances liberal based, and the non-balanced secure-based patterns of parent-child relationship. Data were analyzed by the SPSS using one-way ANOVA. Results:The results showed that the mother-child pattern of the relationship influenced on the child’s social adjustment, while there was no significant influence for the father-child pattern of the relationship. Conclusion: It should be taken into account that the results of this study shows the social adjustment in young ages and before being independent from the family, but the secure-based pattern essentially does not train individuals with high social adjustment.